In-vitro evaluation of probiotic properties of some Bacillus strains isolated from catfish in Makurdi, Nigeria - Kolndadacha, OD; Abonyi, FO; Omeje, VO; Eze, DC; Ezema, C (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was designed to evaluate potential probiotic bacteria isolated from indigenous freshwater catfish (Clarias anguillaris) for productive performance and health status of catfish. The potential probiotic bacteria (Bacillus species) were isolated and identified from the skin and intestine of catfish (C. anguillaris) using standard procedures. The identified identified Bacillus species were screened for probiotic properties such as antagonistic (inhibitory) properties, bacteriocin production ability, pH and bile tolerance, amylolytic; protease and lipolytic activities and virulence tests were performed using standard procedures. Successful bacteria were molecularly characterized using polymerase chain reaction (PCR) and sequenced for definitive identification. Species with DNA sequences that matched closely with typed probiotics from National Center for Bioinformatics (NCBI) data base were picked as potential probiotic bacteria. Ninety (90) and eighty-six (86) bacterial species from skin and intestine respectively were recorded. Five (5) and eleven (11) Bacillus species from skin and intestine respectively were subjected for screening for probiotic potentials. All the Bacillus species isolated, characterized in this study showed positive response to the probiotic properties as potential probiotic bacteria. All the Bacillus species inhibited more than 1 indicator organism with minimum of 11 mm diameter zone of inhibition (DZI) during antagonistic test and all possess potentials of bacteriocin production except Bsp4 and Bsp7.